Trade and Integration in the Caribbean - Egoume Bossogo, Philippe (IMF Working Papers; Working Paper ;, 2002)
This paper analyzes trade in the Caribbean community (CARICOM) using a gravity model framework. The paper seeks to shed light on the dynamics of trade among CARICOM member countries, as well with the rest of world over 1980-99. Overall, the results show that intra-CARICOM trade has increased, suggesting that further regional integration is desirable. At the same time, CARICOM's trade with the rest of the world has risen as well, fueled notably by the reduction of the arrangement's common external tariff and despite the negative impact of the declining preferential access to EU markets for banana. In contrast, WTO membership does not appear to have had a positive impact on trade. Overall, it appears that trade liberalization is consistent with greater CARICOM trade integration.